Femur Intertrochanteric Fractures, - Kılıç, B., Zekioğlu, A., Yücel, A. S., Çatıkkaş, F. (My University, 2014)
Fractures that occur in the area between large and small trochanter are called intertrochanteric femur fractures. Beside femur neck fractures, intertrochanteric femur fractures are one of the most significant health problems seen in old patients. Over 75% of intertrochanteric fractures occur as a result of simple falls while walking or standing. For intertrochanteric fractures, bipolar leinbach endoprosthesis is the priority treatment option, which is applied easily without any need for further equipment such as much scopy or traction, and allows for mobility in a postoperative short time. Being an easy, effective and safe biological diagnosis method and preferred especially in high risky cases, it also ensures bone setting with little damage to periphery tissue through closed reduction and external fixator. In our study, we involved 38 patients with traumatic femur intertrochanteric fractures to whom we applied partial leinbach endoprosthesis. Patients with intertrochanteric fractures who applied late following the fracture were not included in our study. All of our patients were operated and mobilized in 48 hours following the fracture, and no serious complications occurred.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Femur Intertrochanteric Fractures; Patient; Traumatic